Reduction of chemical oxygen demand in domestic wastewater through bioaugmentation (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
The high organic load in domestic wastewater hinders its treatment. Bioaugmentation, through the use of microorganisms, can enhance the degradation of organic matter. This study evaluated the ability of different microbial consortia to reduce Chemical Oxygen Demand (COD) in wastewater treated under laboratory conditions. Consortia obtained from biodigester sludge (BDG), constructed wetlands (H), compost leachate (COMP), intestines of Hermetia illucens (BSF), and mountain microorganisms (MM) were tested and compared against an uninoculated control. Trials were performed in triplicate, measuring COD over 10 days. MM achieved the greatest reduction (42 %), followed by BDG (35 %), whereas H, COMP, and BSF did not outperform the control. Molecular identification revealed genera such as Clostridium, Pseudomonas, and Klebsiella. The results suggest that ecological origin influences degradative efficiency and highlight biodigesters and fermentative preparations as promising sources for decentralized bioaugmentation.